2022
DOI: 10.1113/jp283209
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and skeletal muscle microRNA profiles are more sensitive to sustained aerobic exercise than energy balance in males

Abstract: MicroRNAs (miRNAs) regulate molecular processes governing muscle metabolism. Physical activity and energy balance influence both muscle anabolism and substrate metabolism, but whether circulating and skeletal muscle miRNAs mediate those effects remains unknown. This study assessed the impact of sustained physical activity with participants in energy balance (BAL) or deficit (DEF) on circulating and skeletal muscle miRNAs. Using a randomized cross‐over design, 10 recreational active healthy males (mean ± SD, 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Circulating microRNAs are considered non-invasive biomarkers of such adaptive changes in muscle and other tissues, because their levels are often responsive to various physiological stimuli. Consistent with the work of other research groups (D'Souza et al, 2018), Margolis et al (2022) demonstrated downregulation of many circulating microRNAs, in addition to changes in microRNA levels in skeletal muscle, suggesting a circulating micro-RNA blueprint characterizing changes in response to exercise and less so in response to energy deficiency. Although circulating microRNAs are often considered by-products of cell activity, such as cell death, it is likely that the release of micro-RNAs is a regulated process, and micro-RNAs can act as messengers between cells and tissues, contributing to adaptation at the level of multiple tissues.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Circulating microRNAs are considered non-invasive biomarkers of such adaptive changes in muscle and other tissues, because their levels are often responsive to various physiological stimuli. Consistent with the work of other research groups (D'Souza et al, 2018), Margolis et al (2022) demonstrated downregulation of many circulating microRNAs, in addition to changes in microRNA levels in skeletal muscle, suggesting a circulating micro-RNA blueprint characterizing changes in response to exercise and less so in response to energy deficiency. Although circulating microRNAs are often considered by-products of cell activity, such as cell death, it is likely that the release of micro-RNAs is a regulated process, and micro-RNAs can act as messengers between cells and tissues, contributing to adaptation at the level of multiple tissues.…”
supporting
confidence: 87%
“…Sannicandro et al, 2020). Margolis et al (2022) demonstrated that among microRNAs upregulated in skeletal muscle mainly after exercise, with a few microRNAs responsive to energy imbalance, were microRNAs associated with processes known to be involved in muscle adaptation to exercise. In addition, the authors performed analysis of mRNA levels of predicted targets of altered microRNAs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the exercise, baseline blood and muscle samples from a biopsy of vastus lateralis were collected following a 10 h overnight fast and labelled as PRE (Margolis et al. 2022). Immediately post‐exercise, another blood sample was taken, and a muscle biopsy was performed, and labelled as POST.…”
Section: Strenuous Activitymentioning
confidence: 99%
“…Prior to the 72 h of exercise, each participant had their glycogen levels standardized in 48 h (Margolis et al. 2022).…”
Section: Strenuous Activitymentioning
confidence: 99%